IMPACT OF EXTERNAL DEBTS ON ECONOMIC GROWTH IN NIGERIA - Ibrahim Yinka Agbeyinka (Gusau Journal of Accounting and Finance, 2025)
The study examined the impact of external debts on economic growth in Nigeria. Annual time-series from 2001 to 2022, sourced from Central Bank of Nigeria, Nigerian Exchange Group and Securities Exchange Commission, are adopted. The data was subjected to linear regression analysis which was used to estimate the parameters of the model. The findings revealed that external debts services, debts services costs, and exchange rate fluctuations all have a negative relationship with economic growth. This highlights that higher burdens of external debt servicing and greater exchange rate volatility are associated with reduced economic growth. Thus, the study recommends that government should implement robust debt management strategies that prioritize sustainable debt levels and efficient servicing, The government should introduce policies aimed at stabilizing exchange rates to reduce volatility. Moreso, they diversify the economy, especially by promoting sectors less susceptible to external shock, to reduce dependence on external factors that could exacerbate debt and exchange rate vulnerabilities.